1994
DOI: 10.1152/ajpregu.1994.266.6.r1723
|View full text |Cite
|
Sign up to set email alerts
|

Renin release in rats during blockade of nitric oxide synthesis

Abstract: The influence of renal perfusion pressure on renin release was examined in rats administered the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME). Compared with the control plasma renin of 6.0 +/- 0.7 ng angiotensin I (ANG I).ml-1.h-1, plasma renin activity was suppressed (1.8 +/- 0.2 ng ANG I.ml-1.h-1, P < 0.05) in L-NAME-treated animals in which the renal perfusion pressure was permitted to increase and reached 141 +/- 8 mmHg. Plasma renin activity also was suppressed (2.5 +/- 0.4 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…4), however, does not suggest that the increase of blood pressure was the singular mechanism by which NOS inhibition blunted the increase of renin mRNA levels in response to losartan and ramipril. This hypothesis is supported by recent findings of Johnson and Freeman (41), who demonstrated that the NOinduced stimulation of the renin system is independent of blood pressure changes. Moreover, inhibition of NOS activity also inhibits the renin system in isolated rat kidneys in which the perfusion pressure is kept constant (18,19,21,24).…”
Section: Discussionsupporting
confidence: 75%
“…4), however, does not suggest that the increase of blood pressure was the singular mechanism by which NOS inhibition blunted the increase of renin mRNA levels in response to losartan and ramipril. This hypothesis is supported by recent findings of Johnson and Freeman (41), who demonstrated that the NOinduced stimulation of the renin system is independent of blood pressure changes. Moreover, inhibition of NOS activity also inhibits the renin system in isolated rat kidneys in which the perfusion pressure is kept constant (18,19,21,24).…”
Section: Discussionsupporting
confidence: 75%
“…However, with all of the relevant data taken together, it now appears well established that the overall effect of NO on renin secretion, at least as far as the in vivo situation is concerned, is stimulatory (407,683,765,770).…”
Section: Nomentioning
confidence: 99%
“…First, L-NAME-induced hypertension suppresses plasma renin, eliminating the confounding effects of circulating angiotensin II. 10,11 Second, previous reports indicate that L-NAME treatment activates the renal RAS. 12 Third, we reasoned it would be important to evaluate the role of the renal ACE/angiotensin II Figure 1.…”
mentioning
confidence: 99%